Swimming in a Sea of Shame: Incorporating Emotion into Explanations of Institutional Reproduction and Change - Douglas Creed, W. E.; Hudson, Bryant Ashley; Okhuysen, Gerardo A.; Smith-Crowe, Kristin (Academy of Management Review, 2014)
We theorize the role in institutional processes of what we call the “shame nexus,” a set of shame-related constructs: felt shame, systemic shame, sense of shame, and episodic shaming. As a discrete emotion, felt shame signals to a person that a social bond is at risk, and it catalyzes a fundamental motivation to preserve valued bonds. Systemic shame we conceptualize as a form of disciplinary power, animated by persons' sense of shame—a mechanism of ongoing intersubjective surveillance and self-regulation. We theorize how the duo of systemic shame and sense of shame drives the self-regulation that underpins persons' conformity to institutional prescriptions and institutional reproduction. We conceptualize episodic shaming as a form of juridical power used by institutional guardians to elicit renewed conformity and reassert institutional prescriptions, and also explain how episodic shaming may have unintended effects, including institutional disruption and recreation, when it triggers sensemaking among targets and observers that can lead to the reassessment of the appropriateness of institutional prescriptions or the value of social bonds. We link the shame nexus to three broad categories of institutional work.